An Exploration on the Innovative Model of Bilingual Textbook for International Relations - Wang, Baisong (IJRDO- Journal of Educational Research, 2019)
The bilingual textbook is an important part influencing the equality and effect of bilingual teaching. At present, the four types of textbooks are being used in the bilingual teaching of international relations in colleges and universities in China, including original-version textbook, photocopying textbook, self-compiled textbook and loose-leaf English teaching materials.